Synthesis of a germylidenide anion from the C-C bond activation of a bis(germylene) - Seow, Celestine (2020)
The synthesis of a germylidenide anion by the C-C bond activation of a bis(germylene) is described. The reaction of the 2,6-bis(imino)phenyl bromide 1 with nBuLi, followed by reacting with GeCl2·dioxane, afforded the chlorogermylene [LGeCl] (2, L = 2,6-(HCNtBu)2C6H3). It was then reacted with 1 equiv of lithium in tetrahydrofuran (THF), which proceeded through the reduction of the imine skeleton, along with the C-C bond formation, to afford the bis(germylene) [2-(HC-NtBu)-6-(HC-NtBu)C6H3Ge:]2 (3). It was further reacted with 2 equiv of lithium in THF, which proceeded through the reduction of the germanium(II) centers, followed by the homolytic cleavage of the C-C bond, to form the lithium germylidenide [LGeLi]2 (4). Compounds 2-4 were characterized by NMR spectroscopy and X-ray crystallography. Their bonding natures were also investigated by theoretical studies.